Electrochemical and Mechanistic Study of Superoxide Elimination by Mesalazine through Proton-Coupled Electron Transfer - Tatsushi Nakayama; Ryo Honda (MDPI AG, 2021)
The elimination of superoxide radical anions (O2•−) by 5-amino-2-hydroxybenzoic acid (mesalazine, 5-ASA), 4-amino-2-hydroxybenzoic acid (4-ASA), and related compounds used for ulcerative colitis treatment was investigated using cyclic voltammetry and electron spin resonance (ESR) analyses aided by density functional theory (DFT) calculations. Quasi-reversible O2/O2•− redox was found to be modified by the compounds, suggesting that an acid-base reaction in which a hydroperoxyl radical (HO2•) is formed from O2•− occurs. However, the deprotonated 5-ASA anion can eliminate O2•− through proton-coupled electron transfer (PCET), forming a radical product. This electron transfer (ET) was confirmed by ESR analysis. The 4-aminophenol moiety in 5-ASA plays an important role in the PCET, involving two proton transfers and one ET based on π-conjugation. The electrochemical and DFT results indicated that O2•− elimination by 5-ASA proceeds efficiently through the PCET mechanism after deprotonation of the 1-carboxyl group. Thus, 5-ASA may act as an anti-inflammatory agent in the alkali intestine through PCET-based O2•− elimination.